PENGARUH BUDAYA ORGANISASI, PENGEMBANGAN KARIR DAN KOMPENSASI TERHADAP KINERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH KOTA MAKASSAR - Kartini Jafar; Mashur Razak; Syamsul Alam (Nobel Management Review, 2020)
This study aims to determine and analyze (1) the effect of organizational culture, career development, and compensation partially and simultaneously (2) the most dominant variable affects the staff’s performance of the Regional Disaster Management Agency in Makassar. This study was a quantitative study with 89 respondents as staff from Regional Disaster Management Agency in Makassar. In this study the entire population was made respondent. Data were analyzed using multiple linear regression analysis technique. The results of the analysis indicate that (1) Organizational Culture and Compensation have no partial effect on the Staff’s Performance while Career Development has a positive and significant effect on the staff’s Performance of the Regional Disaster Management Agency in Makassar (2) Organizational Culture, Career Development, and Compensation simultaneously have a significant effect toward the staff’s Performance of the Regional Disaster Management Agency in Makassar (3) Career Development is the most dominant variable affects the staff’s Performance of the Regional Disaster Management Agency in Makassar.